PENGARUH KARAKTERISTIK ORGANISASI, DUKUNGAN ORGANISASI DAN PERSON ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASI - Maludin Panjaitan; Selamat Siregar (Universitas Methodist Indonesia, 2023)
Commitment is one of the most important qualities that an employee should not be able to sell anymore. Therefore, increasing the professionalism of human resources needs to be combined with commitment. The aim of the research is to know the impact of organizational characteristics, organization support and person organization fit on organization commitments PT. X. The sample number is 68 employees PT. X. The results of the survey obtained the characteristics of an organization having a significant influence on the commitment of the organization, the organization's support has a significant impact on the organisation's commitment, the person's organization fit has a substantial impact on organizational commitments, organizational characteristics, organization support and person organization fit together have a significant effect on organisational commitment and the magnitude of organizational features, the support of the organisation and person organisation fit on organization commitments by 89.2% with the remaining 10.8% described by other variables not discussed in this study. Organization Characteristics, Organization Supporti, Person Organization Fit, Organization Commitment.